Conflicting views?: how personal attitudes and perceived public opinion towards formal childcare differ - Beringer, Samira; Bujard, Martin; Diabaté, Sabine (Families, relationships and societies, 2025)
This study investigates how the transition to parenthood is associated with shifts in personal attitudes and perceived public opinion towards formal childcare for children under three years. Using German panel data, we analyse those changes during the family formation phase using panel regressions with linear between-within (hybrid) models. The results for within-components suggest that cultural perceptions are strongly influenced by lifecourse events. After the birth of the first child, parents are less sceptical about daycare for children under three; however, we did not find any systematic changes in perceived public opinion. Between-components reveal that women, though less sceptical themselves, are more likely to perceive societal scepticism. There is an increasing divergence between personal attitudes and the perception of public opinion regarding formal childcare. This points to a conflict between the desire to use formal childcare and societal expectations, which has strong implications for gender equality.
Online veröffentlicht: 09. Juni 2025
Gesehen am 16.10.2025